Segregated oceanic crust trapped at the bottom mantle transition zone revealed from ambient noise interferometry - Jikun Feng (Nature Portfolio, 2021)
By combining ambient noise interferometry with mineral physics modeling, this work sheds new light on mantle transition zone physics. Their findings provide new evidence of segregated oceanic crust subducted and trapped within the mantle transition zone, implying complex mantle circulation modes.